"This is not where we live": The Production of National Citizenship and Borderlines in Sharon Pollock’s The Komagata Maru Incident - Kelly, Erica (Studies in Canadian Literature, 2008)
Sharon Pollock’s play The Komagata Maru Incident (1964) depicts the May 1914 arrival and subsequent turning away of the Komagata Maru — a ship carrying 376 Indian emigrants to the coast of British Columbia. It restages this moment of national boundary marking and invites audience members to reconsider their seats on the sidelines. Pollock recognizes the national border as a location from which she can productively question regulations of belonging and begin to trouble assumptions of national identity. Theorists such as Judith Butler, Vijay Mishra, and others have identified this effect of the inhabitation of border regions. Pollock also explores the potential of borders within the psyche of her characters, notably William Hopkinson, a "borderline Canadian," who was partly responsible for managing the 1914 crisis.